A STUDY OF PERISTALTIC FLOW OF A COUPLE STRESS FLUID IN AN INCLINED CHANNEL UNDER THE EFFECT OF MAGNETIC FIELD - Manikrao, Navarang (ShodhKosh: Journal of Visual and Performing Arts, 2023)
In this paper we study the peristaltic flow of a couple stress fluid in an inclined channel with the effect of magnetic field.